Derywacja czasowników w rosyjskim slangu młodzieżowym na bazie angielskiego materiału leksykalnego - Katarzyna Kubecka (Studia Rossica Posnaniensia)
The article is devoted to the derivation of verbs in Russian youth slang, based on English lexical material (verbs, nouns, adjectives). By means of Russian's numerous affixes, young people form various expressive and humorous verbs, build derivational nests and create English verbs, which are homonyms of Russian words.